Capital social e capital humano : subordinação ou independência? Uma análise a partir do estudo de caso dos conselhos municipais de Macaé e Resende - Santos, Caroline (2008)
The analysis of the correlation between social capital and human capital has gained much attention on the international literature in the past few years. In Brazil, this literature is less difused. The present work has the goal to verify the relation between the social capital and the human capital, after the analysis of a case study carried out with members of the Municipal Councills from Macaé and Resende, using indicators of social capital that acquire its associative dimension. The associativism is considered as the central dimension of the social capital, wich is a definition of a specific concept that develops based on the presentation of a preliminary theoretical outline.